Discrete element modelling of methane hydrate soil sediments using elongated soil particles. (December 2016) - Yu, Yanxin; Cheng, Yi Pik; Xu, Xiaomin; Soga, Kenichi
Abstract: In this discrete element modelling research, triaxial compression tests of particle assemblies were simulated to study the mechanical behaviour of methane hydrate sediments with two different hydrate formation patterns: pore-filling and cementation. The soil particles were modelled using spherical or elongated particles (two aspect ratios 1.5 and 2.0). Hydrates were modelled as smaller particles and were placed either inside the pores in a random manner (the pore-filling case) or around the soil particle contacts (the cementation case). Compared to the pure soil samples, the hydrates essentially influenced the mechanical behaviour of the hydrate-bearing soil samples, and the behaviours varied due to the different hydrate growth patterns. The behaviour with elongated soil particles is much closer to that of the natural hydrate-bearing sandy sediments retrieved from the Nankai Trough than the behaviour with spherical particles. The observed macroscopic strength behaviour is also explained by the microscopic contact-type related contributions (soil–soil contact, soil–hydrate contact and hydrate–hydrate contact) to the deviatoric stresses.